Case report: The diagnostic challenge of primary cardiac intimal sarcoma - Ye, Naili; Lan, Lan; Hu, Huijuan; Liu, Jinping; Xu, Haibo (Frontiers in Cardiovascular Medicine, 2023)
Primary cardiac intimal sarcoma, an extremely rare cardiac tumor subtype, is often mis-diagnosed owing to its rarity and non-specific clinical and radiological features. We report a case of cardiac intimal sarcoma mimicking atrial myxoma in which the clinical presentation and multimodality imaging are described in detail, and diagnostic challenges are highlighted.